1970
DOI: 10.1136/bmj.3.5720.421
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Prednisone in Adult Patients with the Nephrotic Syndrome

Abstract: Organization of TrialThe nephrotic syndrome was considered to be present when all the following criteria were met: (a) oedema-still present or recently observed; (b) proteinuria-5 g. or more per day, measured by biuret or turbidimetric method, not Esbach's method; and (c) hypoproteinaemia-serum albumin less than 3 g./100 ml. Only those patients were admitted to the trial who: (a) were aged 15 or over; (b) had suffered from the nephrotic syndrome, as defined above, for not more than one year; (c) had not been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
2
1

Year Published

1972
1972
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(87 citation statements)
references
References 1 publication
1
83
2
1
Order By: Relevance
“…The work by Coggins 26 compared alternate-day prednisone (average dose=125 mg/d) for 2 months with placebo in 28 adult MCD patients. As observed in the work by Black et al, 25 steroid-treated patients remitted more rapidly, with 12 of 14 treated patients in complete remission before 2 months compared with 6 of 14 controls. However, there was no difference in overall remission rates over 77 months of follow-up.…”
Section: Efficacysupporting
confidence: 66%
See 2 more Smart Citations
“…The work by Coggins 26 compared alternate-day prednisone (average dose=125 mg/d) for 2 months with placebo in 28 adult MCD patients. As observed in the work by Black et al, 25 steroid-treated patients remitted more rapidly, with 12 of 14 treated patients in complete remission before 2 months compared with 6 of 14 controls. However, there was no difference in overall remission rates over 77 months of follow-up.…”
Section: Efficacysupporting
confidence: 66%
“…18,19 Controlled Trials of Corticosteroid Use in Adults with MCD There are two randomized trials that have explored the use of corticosteroids in adults with MCD. In 1970, Black et al 25 published a multicenter controlled study comparing prednisone (at least 20 mg/d for at least 6 months) with no steroid treatment in 125 adults with NS, 31 of whom had MCD. The steroid group showed a rapid decrease in proteinuria and improvement in edema within the first month of treatment compared with control.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly proteinuria has been reported to disappear on treating the cause of the amyloid (Lowenstein and Gallo, 1970) and the rate of renal damage will certainly be decreased. Secondly, although some series have shown no response of membranous nephropathy to steroids either alone (Black, Rose, and Brewer, 1970) or in combination with azathioprine (Rose and Black, 1971), small series in which there has been response to steroid therapy have been reported (Rastogi, Hart-Mercer, and Kerr, 1969;Bariety, Samarcq, Lagrue, Fritel, and Milliez, 1968). The use of these drugs with their potentially dangerous side effects should be avoided whenever possible, and some workers even consider that steroids may actually accelerate the progress of renal amyloid deposition (Cohen, 1967), although Maxwell, Adams, and Goldman (1964) found no evidence of either improvement or deterioration with this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For years it was held that glucocorticoids were potentially ulcerogenic, but recent reviews of randomized, double-blind trials provide no support for this contention (3,4). As Conn and Blitzer (4) point out however, the lack of proof for an association between glucocorticoids and peptic ulcers does not summarily exclude a role for steroids in ulcerogenesis because in controlled trials an increased incidence of peptic ulcers was observed in patients with nephrotic syndrome (5) or cirrhosis (6) who received glucocorticoids, or in other patients receiving a total dose which exceeded 1,000 mg. It has been suggested that the reduced serum binding capacity resulting from the hypoalbuminemia in nephrosis and cirrhosis may lead to high blood levels of unbound steroids.…”
Section: Introductionmentioning
confidence: 98%